Endoscopic ultrasound-guided fine needle aspiration of peritoneal nodules in patients with ascites of unknown cause - Rana, S. S.; Bhasin, D. K.; Srinivasan, R.; Singh, K. (Endoscopy, 2011)
Ascites can pose a difficult diagnostic problem and in some patients, despite extensive work-up, diagnostic laparoscopy or laparotomy is required. We evaluated the usefulness of endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) of peritoneal nodules in 12 patients with undiagnosed ascites (9 men, 3 women; mean [SD] age 47.5 [11.8] years). On EUS, peritoneal deposits, noted as hyperechoic rounded lesions compared with surrounding anechoic ascitic fluid, were observed in 10 /12 patients (83.3 %). Cytological examination of EUS-FNA samples from these deposits revealed metastatic adenocarcinoma in four patients, poorly differentiated carcinoma in one patient and pseudomyxoma peritonei in one patient. It also revealed inflammatory cells without granulomas in four patients, and polymerase chain reaction (PCR) for Mycobacterium tuberculosis was positive in 2 /4 patients (50 %). Deposits were larger and clearly defined in malignant ascites in comparison with tubercular ascites. No complications of EUS-FNA were observed.